1982
DOI: 10.1111/j.1748-5827.1982.tb01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperviscosity syndrome with IgM monoclonal gammopathy and hepatic plasmacytoid lymphosarcoma in a cat

Abstract: A 19‐month‐old cat investigated because of depression, anorexia, polyuria, and polydipsia was found to have hepatomegaly, retinal haemorrhages, and distended tortuous retinal veins. Prolonged bleeding occurred after venipuncture, and serum was hyperviscous due to an immunoglobulin M monoclonal gammopathy. Prothrombin and activated partial thromboplastin times were prolonged, thrombin clotting time was only slightly prolonged and the activities of coagulation factors VII, VIII and IX were normal. The cat died s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…16,17,21,45,46,77 (6) Only 32% of feline MRD specimens were CD79a + in this series. CD79a is expressed from early B-cell progenitors onwards and is variably expressed by human myeloma cells.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…16,17,21,45,46,77 (6) Only 32% of feline MRD specimens were CD79a + in this series. CD79a is expressed from early B-cell progenitors onwards and is variably expressed by human myeloma cells.…”
Section: Discussionmentioning
confidence: 78%
“…33 Since then, a diverse array of sometimes confusing terminology and diagnostic criteria have been used for feline MRD, including multiple myeloma, lymphoma, plasmacytoid lymphosarcoma, plasma cell dyscrasia, plasmacytoma, plasma cell sarcoma, and plasma cell tumor. 18,20,30,51,52,62,77 In a previous report, 49 we classified reported feline MRD in the following diagnostic categories: 1) myeloma (intramedullary or combined intra-and extramedullary involvement), 49 2) cutaneous extramedullary plasmacytoma (CEMP), 49 3) noncutaneous extramedullary plasmacytoma (NCEMP), 49 4) solitary plasmacytoma of bone (SPB), 50 5) IgM (Waldenströ m's) macroglobulinemia, 45,77 6) immunoglobulin secreting lymphoma (IgSL), 17 and 7) myeloma cell leukemia. 19,54,59 Few publications describe the cytologic or histologic features of feline MRD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although results in that study revealed that affected cats most commonly had paraproteinemia and bone marrow plasmacytosis, the authors suggested that bone marrow aspirates and serum protein concentrations should be sufficient for diagnosing multiple myeloma and that diagnostic criteria should also include visceral organ infiltration and atypical plasma cell morphology. 3,4,6,7 The cat of our report met the historical criteria for a diagnosis of multiple myeloma as extrapolated from humans. 5 Bone marrow involvement is used to distinguish between the 2 neoplasms.…”
Section: Discussionmentioning
confidence: 82%
“…[1][2][3] Radiation therapy was discussed with the owners and declined. [1][2][3] Radiation therapy was discussed with the owners and declined.…”
mentioning
confidence: 99%